2018
DOI: 10.1113/ep086844
|View full text |Cite
|
Sign up to set email alerts
|

Functional high‐intensity exercise training ameliorates insulin resistance and cardiometabolic risk factors in type 2 diabetes

Abstract: Functional high-intensity training (F-HIT) is a novel fitness paradigm that integrates simultaneous aerobic and resistance training in sets of constantly varied movements, based on real-world situational exercises, performed at high-intensity in workouts that range from ∼8 to 20 min per session. We hypothesized that F-HIT would be an effective exercise mode for reducing insulin resistance in type 2 diabetes (T2D). We recruited 13 overweight/obese adults (5 males, 8 females; 53 ± 7 years; BMI 34.5 ± 3.6 kg m , … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
52
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 62 publications
(87 reference statements)
2
52
0
1
Order By: Relevance
“…More recently, Nieuwoudt et al [ 69 ] and Fealy et al [ 70 ] provided insight to the effect of 6-weeks of HIFT on beta-cell function [ 69 ] and insulin resistance [ 70 ] among a group of overweight/obese individuals with type 2 diabetes mellitus. Investigators reported significant improvements in beta-cell function and insulin processing [ 69 ], and insulin sensitivity [ 70 ].…”
Section: Utilization Of Hift Programs In the General Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, Nieuwoudt et al [ 69 ] and Fealy et al [ 70 ] provided insight to the effect of 6-weeks of HIFT on beta-cell function [ 69 ] and insulin resistance [ 70 ] among a group of overweight/obese individuals with type 2 diabetes mellitus. Investigators reported significant improvements in beta-cell function and insulin processing [ 69 ], and insulin sensitivity [ 70 ].…”
Section: Utilization Of Hift Programs In the General Populationmentioning
confidence: 99%
“…More recently, Nieuwoudt et al [ 69 ] and Fealy et al [ 70 ] provided insight to the effect of 6-weeks of HIFT on beta-cell function [ 69 ] and insulin resistance [ 70 ] among a group of overweight/obese individuals with type 2 diabetes mellitus. Investigators reported significant improvements in beta-cell function and insulin processing [ 69 ], and insulin sensitivity [ 70 ]. In addition, and similar to other studies with healthy populations, Nieuwoudt and colleagues also reported significant improvements in oxygen capacity (2.43 ± 0.12 vs. 2.81 ± 0.15 L/min pre and post, respectively) and physical performance (223 ± 12 vs. 282 ± 11 repetitions pre and post, respectively) after 6-weeks of training.…”
Section: Utilization Of Hift Programs In the General Populationmentioning
confidence: 99%
“…Incorporating traditional ‘cardio’ training with resistance training is one promising area where such a hybrid‐style of brief vigorous exercise may be a time‐efficient exercise model for improving fitness and metabolic health (Fealy et al . ), including in older individuals (Winett and Ogletree ). The concept of ‘exercise snacks’, whereby isolated, short bouts (∼20 s) of vigorous exercise can be incorporated into the day with several hours of rest in between (Jenkins et al .…”
Section: Introductionmentioning
confidence: 99%
“…The functional high‐intensity training programme used by Fealy et al. () effectively integrated both trends, and the resultant method is particularly appealing because of its versatility. Variations of the protocol can be done almost anywhere, with minimal need for specialized equipment.…”
mentioning
confidence: 99%
“…The programme also reduced fat mass, diastolic blood pressure, blood lipids (triglyceride and very low-density lipoprotein cholesterol) and metabolic syndrome z-score, and increased basal fat oxidation and plasma adiponectin. Training compliance was >95%, and no injuries or adverse events were reported.The timely report by Fealy et al (2018) will no doubt stimulate additional research on the potential for practical, time-efficient exercise protocols to enhance health-related markers in deconditioned individuals and people with cardiometabolic diseases. The findings demonstrate the feasibility and efficacy of functional high-intensity training in a small group of carefully screened participants under controlled conditions.The subjects were non-smokers with no contraindications for elevated levels of physical activity, based on a detailed medical history and completion of an exercise stress test with 12-lead ECG before participation.…”
mentioning
confidence: 99%